Strategi Pembelajaran Inovatif dalam Meningkatkan Kreativitas Siswa pada Mata Pelajaran Ekonomi - Trinanda, Hesty; Suandi , Suandi; Adipta, Marazaenal (Universitas Qamarul Huda Badaruddin, 2025)
This study aims to analyze the implementation of innovative learning strategies in enhancing students’ creativity in Economics subjects at SMA Negeri 1 Praya Barat. The research focuses on five creativity indicators: fluency, flexibility, originality, elaboration, and sensitivity to problems. The study employs a qualitative method with a case study approach. Participants include an Economics teacher and six tenth-grade students. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings reveal that innovative learning strategies, such as problem-based learning and group discussions, enhance students’ creativity. Teachers act as facilitators who encourage students to think critically, present original ideas, and solve problems creatively. These findings align with the literature that innovative strategies provide opportunities for students to explore and collaborate.